Factors influence recycling intention among university students / Zatul Himmah Abdul Karim ... [et al.] - Abdul Karim, Zatul Himmah; Hasan, Zuhairah; Sauid3, Muna Kameelah; Mustakim, Nurul Ain; Mokhtar, Noorzalyla; Ebrahim, Zarina Begum; Mohamad Roseli, Nur Hazwani (Universiti Teknologi MARA, Perlis, 2023)
The recycling programs in Malaysia have been initiated since the early 1990s. Unfortunately, findings indicated that only five per cent of households' practices are being recycled. Hence, by adopting the Theory of Planned Behavior (TPB), this study aimed to investigate the factors influencing recycling intention among university students in Malaysia. Hypothetically, six factors influence the recycling intention behaviour: attitude, past recycling experience, subjective norms, perceived behavioural control, moral norms, and convenience of availability recycling infrastructure. This study used nonprobability sampling to obtain information from 80 randomly selected samples among university students. The data obtained were analysed using descriptive, correlation, and regression analyses. The findings showed that all the investigated antecedents significantly correlate with the recycling intention among university students. The findings also showed that the regression is significant, and 68% of recycling intention is jointly determined by attitude, subjective norm, moral norms, the convenience of availability of recycling infrastructure, previous recycling experience and perceived behavioural control. Even though the study's findings are not generalisable due to limited respondents, the findings can provide future direction of research and offer policymakers valuable information to develop an effective policy related to recycling in Malaysia.